2021
DOI: 10.1097/ccm.0000000000004899
|View full text |Cite
|
Sign up to set email alerts
|

Surviving Sepsis Campaign Guidelines on the Management of Adults With Coronavirus Disease 2019 (COVID-19) in the ICU: First Update

Abstract: BACKGROUND:The coronavirus disease 2019 pandemic continues to affect millions worldwide. Given the rapidly growing evidence base, we implemented a living guideline model to provide guidance on the management of patients with severe or critical coronavirus disease 2019 in the ICU. METHODS:The Surviving Sepsis Campaign Coronavirus Disease 2019 panel has expanded to include 43 experts from 14 countries; all panel members completed an electronic conflict-of-interest disclosure form. In this update, the panel addre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
379
0
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 338 publications
(400 citation statements)
references
References 54 publications
9
379
0
12
Order By: Relevance
“…However, later studies in the first wave showed the risk of aerosolization was limited even when using HFNO at flow as high as 60 L/min ( 9 ). All these results show substantial, progressive, and evidence-driven modification in the management of COVID-19 in our hospital, and internationally ( 7 , 10 ).…”
supporting
confidence: 59%
See 1 more Smart Citation
“…However, later studies in the first wave showed the risk of aerosolization was limited even when using HFNO at flow as high as 60 L/min ( 9 ). All these results show substantial, progressive, and evidence-driven modification in the management of COVID-19 in our hospital, and internationally ( 7 , 10 ).…”
supporting
confidence: 59%
“…In addition, remdesivir was also recommended in patients with oxygen support in the first and subsequent second waves of the COVID-19 pandemic ( 6 ). In contrast, hydroxychloroquine was not recommended by the time of the second wave due to the lack of evidence ( 7 ). Finally, high-flow nasal oxygen (HFNO) was initially suspected to aerosolize severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) in room air ( 8 ), and its use was limited to flows under 30 L/min.…”
mentioning
confidence: 99%
“…Although there is additional conflicting evidence regarding use of remdesivir in COVID-19, it is currently approved by the United States Food and Drug Administration for the treatment of COVID-19 in appropriate hospitalized patients requiring supplemental oxygen but are not requiring mechanical ventilation 7,9,10 . Remdesivir is an adenosine nucleotide prodrug that is rapidly converted to two initial metabolites (alanine metabolite and nucleoside monophosphate metabolite) 7,11 Since some antivirals and other classes of medications can worsen MG, we had initial hesitancy to prescribe remdesivir in these critically ill patients with SARS-CoV-2 infection.…”
Section: Accepted Articlementioning
confidence: 99%
“…Defined by the WHO criteria for ARDS, sepsis, septic shock or other conditions that would normally require the provision of life-sustaining therapies, such as mechanical ventilation (invasive or non-invasive) or vasopressor therapy [2].…”
Section: Critical Covid-19mentioning
confidence: 99%
“…Severe coronavirus disease 2019 (COVID-19) can manifest as rapid decompensation and respiratory failure with elevated inflammatory markers, resulting in cytokine release syndrome, for which interleukin-6 receptor (IL-6R) antagonists are approved treatments [1][2][3][4]. An interest in IL-6R antagonists and corticosteroids has increased recently due to their potential role as immunomodulators in the treatment of cytokine storms related to COVID-19 [5].…”
Section: Introductionmentioning
confidence: 99%